2012
DOI: 10.1016/j.jfma.2011.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin utility in neonates and children

Abstract: Melatonin (N-acetyl-5-methoxytryptamine) is an endogenously produced indoleamine secreted by the pineal gland and the secretion is suppressed by light. Melatonin is a highly effective antioxidant, free radical scavenger, and has anti-inflammatory effect. Plenty of evidence supports the utility of melatonin in adults for cancer, neurodegenerative disorders, and aging. In children and neonates, melatonin has been used widely, including for respiratory distress syndrome, bronchopulmonary dysplasia, periventricula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 100 publications
3
53
0
1
Order By: Relevance
“…In this study, we found that melatonin restored the levels of hippocampal reln mRNA expression by reducing DNMT1 and MeCP2 binding to the reln promoter. Melatonin has been used in treating compromised pregnancies, including those affected by prenatal stress [23,24]. In our study, we found that melatonin restored the levels of hippocampal reln mRNA expression by reducing DNMT1 and MeCP2 binding to the reln promoter.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…In this study, we found that melatonin restored the levels of hippocampal reln mRNA expression by reducing DNMT1 and MeCP2 binding to the reln promoter. Melatonin has been used in treating compromised pregnancies, including those affected by prenatal stress [23,24]. In our study, we found that melatonin restored the levels of hippocampal reln mRNA expression by reducing DNMT1 and MeCP2 binding to the reln promoter.…”
Section: Discussionsupporting
confidence: 57%
“…Due to its antioxidant properties, it might improve quality of life, reduce healthcare costs, and help reduce complications in the neonatal period [23]. Recently, a study showed that agomelatine, which is a mixed melatonin-1 and -2 receptor/serotonin receptor antagonist, corrects many aspects of pathological epigenetic programming triggered by prenatal stress [24].…”
Section: Introductionmentioning
confidence: 99%
“…6 Following birth its production has been suggested to have a role in brain development and pineal dysfunction was associated with sudden infant death. 7,8 Melatonin supplementation has been studied in adults, children and neonates. It was studied in neonates with respiratory distress syndrome, 9 sepsis 10 and as a preoperative antioxidant.…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, melatonin has been used in pediatrics to treat respiratory distress syndrome, bronchopulmonary dysplasia, seizure disorders and to reduce oxidative stress in sepsis and asphyxia (Gitto et al, 2011, Sanchez-Barcelo et al, 2011, Aversa et al, 2012, Chen et al, 2012). Thus, melatonin may potentially protect against brain injury induced by infection or inflammation, by attenuating the induction of nitrosative and oxidative stress in neonates.…”
Section: Introductionmentioning
confidence: 99%